Carbon Dioxide (CO2) Absorption Process Using Sodium Hydroxide (NaOH) - Aldi Nugroho; Yoga Bekti Susanto; Villia Lidzati Kamilah; Regita Prameswari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
An absorption process can be carried out to reduce carbon dioxide gas emissions in the surrounding environment. Absorption is a contact process between a mixture of gas and liquid that aims to remove one of the gas components by dissolving it in a suitable liquid. In this study, the CO2 absorption process was carried out to determine the effect of CO2 flow rate on the amount of CO2 absorbed with NaOH absorbent. The results showed that the correlation between CO2 flow rate and absorption factor was inverse because an increase in CO2 flow rate caused the contact between CO2 gas and NaOH to decrease. As a result, the absorption factor decreased because the ratio of CO2 was greater than the absorbent. While the relationship between L/V and the absorption factor is directly proportional if the flow rate of the liquid increases, the retained liquid tends to saturate and can accelerate the diffusion of CO2 in the water, so the absorption factor also increases. In addition, after the absorption of CO2 gas, sodium carbonate is produced, which is the result of the reaction of CO2 with NaOH.